Chromophobe adenoma of the pituitary gland in a dog - Sevil Atalay Vural; Oğuz Kul (Eurasian Journal of Veterinary Sciences)
In this report, sinusoidal type of chromophobe adenoma in the pars distalis of pituitary gland was described with gross and microscopic findings in a 7 year-old. Terrier dog. Grossly, it was placed in the base of the brain, in between chiasma oplicum and anterior of pons cerebri. The tumor mass was 1.4x2.0x1.7 cm in diameter, spherical, firm and dark brown in colour. Microscopically, large round shaped chromophobe cells were observed. There were abundant sinusoids which were enlarged and filled with erythrocytes in between Ihese cells. A few rosette fike structures were also present.